Credit risk impact on banking financial performance, most relevant topic to be reseached in society 5,0 era: Bibliometric study - Mulyati, Mulyati; Amir, Ja'far; Fauziah, Layla (Junal Ilmu Manajemen, 2024)
One significant and well studied component of financial system integrity is the connection between bank credit risk and financial performance, as well as the impact of both on banking stability in the 5.0 era of society. The gap in previous research led researcher to make this paper use bibliometric analysis. By utilizing 335 documents, including 202 journals and books, 16.905 references, 294 articles, and 850 authors sources from Scopus. In the time span from 1978 to 2024. Through the used of advanced tools such as biblioshiny, this paper illuminates thematic and intellectual trends. The analysis offers insight into the current reseach landscape. The interconnected dynamics of credit risk on the financial performance of banks is avery relevant topic for research that remains unexplored. Thus, this reseach seeks to uncover this complex relationship. The findings suggest pratical implications that contribute to current trends and hot research topics. Although there are limitations, potential trend transformations are indentified due to the evolving financial system of banking financial performance. This reseach contribute to the scientific discourse in the field. It lays the foundation for future.